Language as an Expression of Anger in Selected Namibian Novels: Masked warrior and Complicated: Language as an Expression of Anger in Selected Namibian Novels: Masked warrior and Complicated - Kambwale, Elizabeth (Journal of Communication and Cultural Trends, 2026)
This article presents a cognitive stylistic study of anger in two Namibian novels: Ndinaelao Moses’ Masked warrior and Malakia Haimbangu’s Complicated. The study evaluated the lexical expressions of anger, figurative expressions, and features of anger discourse. The study applied textual world theory as a theoretical framework for understanding and analysing the texts. The methods of data collection and data analysis were qualitative. The results of the study showed that the texts had manipulated and maintained the readers’ interest through the use of anger. The study found that words about anger are made more offensive by using figurative language terms. Additionally, the study showed that angry language might be used to show defensiveness, sorrow, or arrogance. The study found that creating writings with anger in them makes readers relate to the characters’ real-world experiences. It was further established that the use of figurative phrases to communicate and simplify complex ideas that are challenging to understand was also concluded. The study concluded that discourse influences how angry texts are written. The study suggests the use of alternative language and grammatical expressions that are consistent with Text World Theory, which emphasises the significance of using linguistic and cognitive strategies to create a cohesive and immersive fictional world.